Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1038/s41467-022-28407-4
|View full text |Cite
|
Sign up to set email alerts
|

The induction of peripheral trained immunity in the pancreas incites anti-tumor activity to control pancreatic cancer progression

Abstract: Despite the remarkable success of immunotherapy in many types of cancer, pancreatic ductal adenocarcinoma has yet to benefit. Innate immune cells are critical to anti-tumor immunosurveillance and recent studies have revealed that these populations possess a form of memory, termed trained innate immunity, which occurs through transcriptomic, epigenetic, and metabolic reprograming. Here we demonstrate that yeast-derived particulate β-glucan, an inducer of trained immunity, traffics to the pancreas, which causes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 84 publications
2
43
0
Order By: Relevance
“… 106 In addition, β‐glucan treatment induced a CCR2‐dependent influx of monocytes to the pancreas that display trained immunity profile, and β‐glucan‐treated mice showed reduced tumor burden and prolonged survival in orthotopic models of pancreatic cancer. 107 …”
Section: The Yin‐yang Balance Of Trained Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“… 106 In addition, β‐glucan treatment induced a CCR2‐dependent influx of monocytes to the pancreas that display trained immunity profile, and β‐glucan‐treated mice showed reduced tumor burden and prolonged survival in orthotopic models of pancreatic cancer. 107 …”
Section: The Yin‐yang Balance Of Trained Immunitymentioning
confidence: 99%
“…The research may have broader implications for cancer therapy since a 60‐year follow‐up retrospective clinical trial showed that childhood BCG vaccination was associated with a lower risk of lung cancer development in the United States 106 . In addition, β‐glucan treatment induced a CCR2‐dependent influx of monocytes to the pancreas that display trained immunity profile, and β‐glucan‐treated mice showed reduced tumor burden and prolonged survival in orthotopic models of pancreatic cancer 107 …”
Section: The Yin‐yang Balance Of Trained Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Yan et al induced the activation and infiltration of monocytes and macrophages utilising β-glucan treatment, thereby reducing the tumour burden. 109 Mulder et al constructed a nano-biologic platform loaded with peptidoglycans, stearoyl fatty acid-modified 6- O -acyl muramyl dipeptide, and muramyl tripeptide phosphatidylethanolamine. 110 Given its high bone marrow avidity, this nano-platform could more effectively induce trained immunity.…”
Section: Chemical Strategies For Modulating the Tmementioning
confidence: 99%
“…Additionally, the remarkable LAMP3 gene expression in human regDCs was dismissed in the mouse (56). A similar situation occurred in the CRC/GC mouse model, in which the classification of DC cells was too broad (57,58). Additionally, DC gene expression in esophageal squamous cell carcinoma mouse models mostly does not match that in human tumors (59).…”
Section: The Difference Between Clinical Samples and Tumors From Mous...mentioning
confidence: 99%